TEACHERS’ EMPOWERMENT, SELF-REGULATION AND BEING ISTIQAMAH AS KEY FEATURES OF JOB PERFORMANCE - Laksmi Mayesti Wijayanti; Choi chi hyun; leo hutagalung; Masduki Asbari; Priyono Budi Santoso; Agus Purwanto (Dinasti International Journal of Education Management And Social Science, 2020)
Non-formal education is predicted to be the future backbone in supporting the literacy in highly populated country (Ololube, 2012). Indonesia as one of the E-9 countries have acknowledged the needs to strengthen the non-formal education as one of the key supporting elements in enhancing the education index. Both government and non-government organization have participated actively in establishing the non-formal education to be more accessible and convenience. The fundamental issue is that the teacher quality in education is still below expectation (Baswedan, 2014). Moreover, non-formal education has encountered dilemma in creating optimum performance of their teacher due to its non-profit nature. Nevertheless, it is evidenced that they still manage to deliver their jobs adequately. Therefore, this paper will investigate the determining factors of such unique setting. This study’s instruments are the psychological empowerment scale used by Spreitzer (1995), The Self-Regulation Questionnaire (SRQ) (Brown, Miller, & Lawendowski, 1999), Islamic work ethic scaling (Ali, 1988) and the questionnaire teachers’ job performance self-rating questionnaire (TJPSQ) were developed to measure teachers’ job performance. The result of the study indicates that empowerment and istiqamah have significantly influenced to teachers’ job performance, while self-regulations have no significant effect on Job performance.